Northern Hemisphere Monsoon Response to Mid‐Holocene Orbital Forcing and Greenhouse Gas‐Induced Global Warming. Issue 3 (1st February 2019) - D'Agostino, Roberta; Bader, Jürgen; Bordoni, Simona; Ferreira, David; Jungclaus, Johann
Abstract: Precipitation and circulation patterns of Northern Hemisphere monsoons are investigated in Coupled Model Intercomparison Project phase 5 simulations for mid‐Holocene and future climate scenario rcp8.5. Although both climates exhibit Northern Hemisphere warming and enhanced interhemispheric thermal contrast in boreal summer, changes in the spatial extent and rainfall intensity in future climate are smaller than in mid‐Holocene for all Northern Hemisphere monsoons except the Indian monsoon. A decomposition of the moisture budget in thermodynamic and dynamic contributions suggests that under future global warming, the weaker response of the African, Indian, and North American monsoons results from a compensation between both components. The dynamic component, primarily constrained by changes in net energy input over land, determines instead most of the mid‐Holocene land monsoonal rainfall response. Plain Language Summary: Mechanisms mediating the response of the Northern Hemisphere monsoons are investigated in two different simulated warm climates: the mid‐Holocene driven by orbital perturbations and a future global warming scenario due to increased greenhouse gas concentration. In both climates, monsoons wetten and expand relative to present day. In general, they do so more in the past than in the future despite a large warming in the latter. To understand these different responses, we explore whether monsoon changes are mostly related to changes in the amount of water vapor held in the atmosphere or to changes in the mean atmospheric circulation. In the past, intensification of monsoons is due to the reinforcing effects of increased water vapor content and strengthening of the mean circulation. In the future, however, the mean circulation weakens, opposing the water vapor content increase and leading to an overall weaker response than in the past. Causes for this difference can be traced back to changes in the net energy input into the atmosphere: While, in the past, this energy input increases, notably over Northern Hemisphere land, it remains largely unchanged in the future climate. Our results highlight that mid‐Holocene is not an analogue for future global warming scenario. Key Points: Different mechanisms mediate the response of Northern Hemisphere monsoons under future global warming and mid‐Holocene forcing Northern Hemisphere monsoons intensify more strongly in mid‐Holocene than in future climate despite a larger warming in the latter As an emergent constraint for future projections, tropical circulation weakening limits monsoon rainfall increase with global warming